2015
DOI: 10.1128/microbiolspec.uti-0016-2012
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Physiology of the Urinary Tract: Relation to Host Defense and Microbial Infection

Abstract: The urinary tract exits to a body surface area that is densely populated by a wide range of microbes. Yet, under most normal circumstances, it is typically considered sterile, i.e., devoid of microbes, a stark contrast to the gastrointestinal and upper respiratory tracts where many commensal and pathogenic microbes call home. Not surprisingly, infection of the urinary tract over a healthy person’s lifetime is relatively infrequent, occurring once or twice or not at all for most people. For those who do experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 161 publications
(165 reference statements)
0
40
0
2
Order By: Relevance
“…While the role of type 1 fimbriae in virulence is unknown, it is well defined that specific adherence and increased induction of mucosal inflammation are the mechanisms used by P fimbriae to increase the virulence of UPEC (Connell et al, 1996). Significant association (p-value 0.006) was found between fimH gene and gender; this association may be due to difference in anatomical structure of urinary tract between male and female (Hickling et al, 2015). The results confirmed the existence of aer gene with more prevalence in diarrheal isolates, this finding totally agreed with Oswald et al (1991), who found that aer gene was positive in 70% of diarrheal samples and Micenková et al (2014) who found aer gene was positive in 68%.…”
Section: Discussionmentioning
confidence: 68%
“…While the role of type 1 fimbriae in virulence is unknown, it is well defined that specific adherence and increased induction of mucosal inflammation are the mechanisms used by P fimbriae to increase the virulence of UPEC (Connell et al, 1996). Significant association (p-value 0.006) was found between fimH gene and gender; this association may be due to difference in anatomical structure of urinary tract between male and female (Hickling et al, 2015). The results confirmed the existence of aer gene with more prevalence in diarrheal isolates, this finding totally agreed with Oswald et al (1991), who found that aer gene was positive in 70% of diarrheal samples and Micenková et al (2014) who found aer gene was positive in 68%.…”
Section: Discussionmentioning
confidence: 68%
“…Furthemore, we have shown that the sequences of intensity and depth of pathological lesions were dependent on the duration of the experiment 18 . Nevertheless, more recent research has shown that the that long-term of HMS exposure leads to increases of HM accumulation level in the UB tissue which influence significantly on the morphometric parameters of organ wall thickness (this data has not been published yet).A lot of simulated studies demonstrated that the organ easily exposed to development of inflammatory diseases of various genesis that accompanied by urodynamic disorders 15,17 . A considerable amount of scientific data on associate disruption of the level of physiological concentrations trace elements with the development of oncological pathology of the bladder and other different organshas been published 9,10,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…An important role in the removal of metabolism products and toxins is given to the urinary bladder (UB). This organ has functional peculiarities and provides long and controlled urine store in its cavity 15 . It is proved that wide range of factors can affect the development of its pathological changes and dysfunctions [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a healthy bladder, the plasma membranes of superficial epithelial cells contain hexagonal arrays of UPK proteins, which are transported by discoidal storage vesicles and multivesicular bodies (MVBs) and are critical for normal epithelial flexibility and barrier function [33,34]. Previous work has demonstrated a role for ATG16L1 in superficial cell vesicular trafficking in mice globally hypomorphic for Atg16l1 [22].…”
Section: Presence Of the Atg16l1 T300a Variant Confers Protection Fromentioning
confidence: 99%